(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: To describe some clinical and paraclinical characteristics of idiopathic central precocious puberty. Subjects and methods: Cross-sectional descriptive study of 60 patients with idiopathic central precocious puberty at Nghe An Obstetrics and Pediatrics Hospital from January 2018 to December 2022. Results: The proportion of girls accounted for 100%, the majority of children diagnosed were in the 6-8 age group. Breast development was the main reason for girls to come to the hospital (83.3%). Breast development was Tanner stage 2 or higher in 100% of girls, 18.3% of girls had pubic hair, 1.7% had menstruation. Girls had bone age advanced over chronological age (2.83 ± 0.73 years), 80% of girls have uterus height ≥ 34 mm. Conclusion: Children with idiopathic central precocious puberty usually appear 6-8 years old. Girls showed breast development. Bone age was older than chronological age, uterus height ≥ 34 mm.